Bioprinted PDLSCs with high-concentrated GelMA hydrogels enhances osteogenic differentiation - Dr Changyong Yuan; Prof Penglai Wang; Ms Wen Wang (Elsevier, 2023)
Aim or Purpose: Regeneration of sensory nerves is challenging in dental pulp regeneration. Schwann cells (SCs) are essential glial cells conducive to regenerating dental pulp sensory nerve, but their source is scarce. This study aimed to explore whether Schwann-like cells derived from dental pulp stem cells (SC-DPSCs) are conducive to the growth of dental pulp sensory nerve axons. Materials and Methods: In the present study, primary human dental pulp stem cells (hDPSCs) were cultured and their multidirectional differentiation ability was detected. hDPSCs were induced into SC-DPSCs using the 3 steps protocol. The expression of MBP, S-100, and P75NTR, and dynamic expression and distribution of BDNF/NT-3 in SC-DPSCs were assessed by quantitative real-time PCR, immunofluorescence and ELISA. Primary trigeminal neurons were cultured and the central neuronal markers NF200, TUBB3 and MAP2 were detected by cellular immunofluorescence. Trigeminal neurons and SC-DPSCs were indirected co-cultured, after that the growth activity of trigeminal neurons was detected by CCK-8. One key factor during the differentiation process of hDPSCs into SC-DPSCs were screened by mRNA sequencing. Results: The results showed that SC-DPSCs significantly expressed characteristic SCs markers and promoted the axon growth of rat trigeminal nerve. High-throughput sequencing found that PTGS2 maybe the key gene participate in the induction process. Conclusions: Taken together, our findings demonstrate the potential of SC-DPSCs in sensory nerve regeneration in dental pulp and dentin complexes. After differentiation into SC-DPSCs, hDPSCs secreted more nerve growth factors BDNF and NT-3, which significantly promoted the growth of trigeminal nerve axons.